2013
DOI: 10.1242/jeb.088682
|View full text |Cite
|
Sign up to set email alerts
|

Mate preference in the painted goby: the influence of visual and acoustic courtship signals

Abstract: SUMMARYWe tested the hypothesis that females of a small vocal marine fish with exclusive paternal care, the painted goby, prefer high parental-quality mates such as large or high-condition males. We tested the effect of male body size and male visual and acoustic courtship behaviour (playback experiments) on female mating preferences by measuring time spent near one of a two-choice stimuli. Females did not show preference for male size but preferred males that showed higher levels of courtship, a trait known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…More recently, Amorim et al (2013a) have found that fatigue (measured as the ratio between the average pulse period observed at the end and the beginning of the mating drum) was very stereotyped in the painted goby (P. pictus) and that it was a good predictor of male size, explaining 45 % of the variability found in this male feature. This increase in resistance to fatigue in larger animals was, however, not found in the congeneric sand goby (P. minutus) that make similar drums but with a higher pulse repetition rate than P. pictus (Amorim et al 2013b), suggesting interspecific differences in physiological constraints in sound production.…”
Section: Acoustic Indicators Of Male Sizementioning
confidence: 74%
See 4 more Smart Citations
“…More recently, Amorim et al (2013a) have found that fatigue (measured as the ratio between the average pulse period observed at the end and the beginning of the mating drum) was very stereotyped in the painted goby (P. pictus) and that it was a good predictor of male size, explaining 45 % of the variability found in this male feature. This increase in resistance to fatigue in larger animals was, however, not found in the congeneric sand goby (P. minutus) that make similar drums but with a higher pulse repetition rate than P. pictus (Amorim et al 2013b), suggesting interspecific differences in physiological constraints in sound production.…”
Section: Acoustic Indicators Of Male Sizementioning
confidence: 74%
“…Painted gobies gravid females that were exposed to a dichotomous choice of courtship sounds versus a control (silence or white noise) did not show a preference for conspecific sounds (Amorim et al 2013b). However, when courtship sound playback was associated with visual access (but not chemical) to a conspecific male, females preferred to affiliate with the male associated with sound than with the control male.…”
Section: Preference For Vocal Malesmentioning
confidence: 91%
See 3 more Smart Citations